Study of electromagnetic processes in the system “contact network—electric locomotive” while reducing the minimum opening angle of the thyristors in the rectifier-inverter converter - Yu. M. Kulinich; D. Yu. Drogolov (Вестник Научно-исследовательского института железнодорожного транспорта, 2020)
A new method is proposed for increasing the power factor of an electric locomotive by changing the minimum opening angle of thyristors α0 of a rectifier-inverter converter. The decrease in the angle α0 is due to changes in both the structure of the transducer and the zone of its regulation. A pulse  synchronization device has been developed that makes it possible to generate pulses with strong distortions of the mains voltage Uc at the points of natural transition of the voltage of the fundamental frequency Uс through the zero line. Based on this device, an α0 pulse-forming device was developed that eliminates the influence of pre- and post-switching voltage fluctuations. A “contact network—electric locomotive” model was created in the environment of MatLab/Simulink, taking into account the nonlinearity of the longitudinal parameters of the contact network. The effect of decreasing the angle α0 on the character of pre- and post-switching voltage fluctuations was analyzed, and the parameters of  transient processes were calculated. Particular attention was paid to modeling the parameters of traction network. The primary network parameters adopted in the model correspond to theoretical parameters for the selected type of contact suspension. Their high convergence is confirmed by the calculation of the coefficient of determination R2. Calculations on the “contact network — electric locomotive” model show that compared with the standard scheme of the electric locomotive, where the minimum opening angle of the thyristors is α0 = 9° el., the decrease in the angle α0 to 4.5° el. leads to an almost twofold decrease in the amplitude of pre-switching voltage fluctuations and a small decrease in the amplitude of post-switching voltage fluctuations. The model results indicate that a decrease in the minimum thyristor opening angle α0 leads to an increase in the power factor of the electric locomotive.